The associations between fasting plasma glucose levels and mortality of COVID-19 in patients without diabetes. (November 2020) - Huang, Yun; Guo, Heming; Zhou, Yan; Guo, Jingjing; Wang, Tiantian; Zhao, Xuming; Li, Hui; Sun, Yihui; Bian, Xuna; Fang, Chen
Abstract: Aims: Coronavirus disease 2019 (COVID-19) which is a novel pneumonia can rapidly progress to acute respiratory distress syndrome, septic shock, and multiple organ dysfunction syndrome. It has appeared in 196 countries around the world. We aimed to clarify the associations between fasting plasma glucose levels and mortality of COVID-19 in patients without diabetes. Methods: We performed a retrospective, single-center study of 151 patients without diabetes in Tongji Hospital from January 1, 2020 to February 28, 2020. Past medical histories, clinical features and laboratory parameters were collected in these patients. Results: Compared with survivors, non-survivors were more likely to have underlying medical conditions including hypertension and chronic pulmonary diseases. Non-survivors had higher C-reactive protein (CRP), procalcitonin (PCT), interleukin (IL)-2R, IL-6, IL-8 and, tumor necrosis factor-α (TNF-α) levels, while lower lymphocyte counts as compared with those of survivors (all P <0.05). Besides, patients with higher fasting plasma glucose (FPG) had higher IL-6, IL-8, CRP levels and mortality; while lower lymphocyte counts. After adjusting for age and gender, each tertile increment of FPG levels conferred 3.54-fold higher risks of death (odds ratio, 3.54; 95% confidential interval, 1.25-10.06, P =0.018). Conclusions: Non-survivors combined with more comorbidities, more severe infection, and worse liver, kidney and cardiac function in patients without diabetes. Additionally, fasting plasma glucose levels were significantly associated with the risk of death in patients even with normal FPG and HbA1c levels.